NP EXTENSION: B&B PHONOTACTICS - Dziubalska-Kołaczyk, Katarzyna (Versita Ltd., de Gruyter, 2009)
This paper will report on an extension of the framework of Natural Phonology in the area of syl- lable phonology and phonotactics. In particular, it will present a universal model of phonotactics constructed within Beats-and-Binding Phonology (B&B Phonology, cf. Dziubalska-Kołaczyk 2002) – a syllable-less theory of phonology embedded in Natural Phonology. The thrust of the theory is the claim that intersegmental cohesion determines syllable structure, rather than being determined by it (if one insists on the notion of the “syllable” which is epiphenomenal here). The core of B&B phonotactics is the Net Auditory Distance Principle, according to which phonologi- cal naturalness of clusters can be evaluated.
Keywords: phonotactics; morphonotactics; beats-and-binding phonology; universal preferences; net auditory distance principle